Layered K(K1.5Eu0.5)Ta3O10 for humidity sensor. (March 2016) - Wang, Jian-Guang; Zhang, Le-Xi; Yin, Jing; Zhao, Li-Xin; Bie, Li-Jian
Graphical abstract: Abstract: Dion–Jacobson structure layered perovskite K(K1.5 Eu0.5 )Ta3 O10 was synthesized using a traditional solid-state reaction. A humidity sensor made from the obtained K(K1.5 Eu0.5 )Ta3 O10 reveals that the sensitivity exhibits good linear response, and the response and recovery time is only about 6 s and 2 s at 85% RH respectively, showing fast response and recovery characteristics. Furthermore, the humidity hysteresis is only 7% RH. All these results indicate that K(K1.5 Eu0.5 )Ta3 O10 can be utilized in high-performance humidity sensors.